Synthesis of 1,2,3-Triazole-Fused Indole Derivatives via Copper-Catalyzed Cascade Reaction - Majeed, Kashif; Liu, Bangjie; Zhou, Fengtao; Zhang, Qiuyu (Synthesis, 2021)
A copper-catalyzed tandem reaction has been developed for the synthesis of 1,2,3-triazole-fused indole derivatives. This protocol allowed us to access a wide range of 1,2,3-triazole-fused indole derivatives in moderate to excellent yields. The 1,2,3-triazole-fused indole derivatives emit blue and greenish light when excited at 365 nm. The products were further explored for their quantum efficiency and photophysical properties.
Keywords: 1,2,3-triazole-fused indoles; [3+2] cycloaddition; C–N bond formation; tandem reaction; sodium azide